PERILAKU INOVATIF UMKM DITINJAU DARI IKLIM SPIRITUALITAS ORGANISASI DAN PEMBELAJARAN ORGANISASI - Nuvriasari, Audita; Candrawati, Krisnita (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
Innovative behavior reflects the activities carried out by individuals or groups to find solutions to a problem by finding new ideas that are applied to SMEs. Innovative behavior can have an impact on the success of MSMEs The purpose of this research is to analyze the influence of the organizational spiritual climate on the innovative behavior of MSMEs with organizational learning as a mediator. The research sample is 200 MSMEs managers in the Special Region of Yogyakarta province. The sampling technique uses purposive sampling. Based on the results of testing the hypothesis with PLS, it can be concluded that the organizational spiritual climate has a significant positive effect on the innovative behavior of MSMEs with organizational learning as a mediator.